Gerência de encaminhamento dinâmico e adaptativo baseado em contexto - MUAKAD, Carlos Frederico Jansen (2015)
The technological evolution has improved the number of interconnected users and devices, besides the number of applications with a growing demand for time-sensitive content. Nevertheless, the current implemented solutions have not been effective in order to ensure the packet delivery quality within communication networks throughout the world. Moreover, in order to support the emerging traffic demand related to applications such as video-on-demand and audio-conference, some issues should be revisited such as congestion, admission control and resources management. Currently, most of the existing solutions available for handling these issues are based on quality of service metrics. However, some features of these emerging applications such as mobility, georeference, among others require a larger amount of resources from the infrastructure which has become inefficient with this higher data load. This situation has caused a negative impact on users’ experience. Therefore, context evaluation, which is based not only on quality of service, but also on experience quality and device’s quality, has become an interesting solution in order to minimize problems related to user’s communication.The concept of context-based networks is discussed in this dissertation through the simulation of a solution for the context-based adaptive routing, considering quality of service metrics such as delay, bandwidth and jitter; quality of experience metric such as MOS (Mean Opinion Score) and; quality of device metrics such as processing power and memory availability. In this work it is possible to demonstrate that, through simulation, that the implementation of context-sensitive networks allows the optimization of network resources utilization and improve the delivery of user demands causing a positive impact on users’ experience.